ON THE "TUNING RUSSIA" PROJECT - Ivan A. Dyukarev; Igor B. Kotlobovsky; Evgenia V. Karavaeva; Artur L. Demchuk; Irina G. Teleshova; Vladimir Kh. Echenike; Maria E. Ulyanova (Moscow Polytechnic University, 2022)
This paper is the first one from the coming soon articles with a description of the results and findings of the project "Tuning of educational structures". The article highlights the main goals and results of the project "Tuning Russia" conducted in Russia in the period of 2010-2013. Special attention is paid to the basic approaches of the drafting the Reference points of the educational programs in different subject areas. Some findings from the survey of the opinion of academy, alumni, students and employers on the importance and achieved level of the professional competencies in Economics are given. The paper describes several kinds of activities to be done by the Tuning centers were established in 13 Russian universities participated in the project "Tuning Russia".